Measuring learners' critical thinking skills using argument-based assessment on the issue of global warming - Wahyu Inda Safitri; Budi Jatmiko; Titin Sunarti; Binar Kurnia Prahani; Muhammad Satriawan (Education and Development Research, 2025)
The low level of students' critical thinking and argumentation skills has attracted attention. This study aims to analyze the improvement of students' critical thinking skills by implementing argumentation-based assessment as an innovative learning strategy. The method used is a quantitative descriptive study involving 28 grade XI MIPA students, using essay tests and questionnaires as data collection instruments. Data were analyzed descriptively and inferentially through N-gain calculations and paired t-tests to measure the improvement of critical thinking skills. The results showed an increase in critical thinking skills from the poor and sufficient categories in the pre-test stage to good and very good categories in the post-test stage, with an average N-gain of 55% which is included in the moderate category and a paired t-test significance value <0.05 which indicates a significant difference. These findings demonstrate the effectiveness of argumentation-based assessment in developing critical thinking skills while contributing to the development of relevant contextual learning strategies to improve scientific literacy and meet the demands of 21st-century competencies.